An analysis of the effects of nanoparticles deposition on characteristics of the heating surface and ON pool boiling of water - Kiyomura, I. S. [UNESP]; Manetti, L. L. [UNESP]; da Cunha, A. P. [UNESP]; Ribatski, G.; Cardoso, E. M. [UNESP] (Elsevier, 2017)
Nanofluid pool boiling can modify the morphology of the heating surface and the physical properties of the base fluids, interfering directly on the vapor bubbles dynamics and on the heat transfer mechanisms. This paper concerns an experimental investigation of the effects of surface roughness and nanoparticle deposition on the contact angle, surface wettability and pool boiling heat transfer coefficient (HTC). Experiments were carried out using copper surfaces with different roughnesses, and deionized water as the working fluid at a pressure of 98 kPa and under saturated conditions. The nanostructured surfaces were produced by maghemite nanoparticle deposition, which is achieved by boiling selected mass concentrations of a Fe2O3-deionized water nanofluid (0.029 g/l and 0.29 g/l, corresponding to low and high nanofluid concentration, respectively). The highest heat transfer coefficients were obtained for the smooth surface with deposition of nanoparticles at low mass concentrations. In addition, as the nanofluid concentration increases the surface roughness also increases, and the higher the nanofluid concentration, the lower the contact angle of water on the coated surface.
Keywords: Boiling heat transfer; Heat transfer coefficient; Nanofluid; Nanostructured surface